New pimarane diterpenes and other antimycobacterial metabolites from anisochilus verticillatus - Kulkarni, Roshan R.; Shurpali, Ketaki; Khedkar, Vijay M.; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2016)
Phytochemical investigation of the acetone extract of the aerial parts of Anisochilus verticillatus afforded a new 8,9-secopimarane diterpene (1), two new isopimarane diterpenes (2, 3) and the known ursolic acid (4), beta-amyrin (5), -amyrin (6), stigmast-5-en-3-one (7) and hydroxychavicol (8). Structures of the new compounds were elucidated with the help of 1D and 2D nuclear magnetic resonance spectroscopic data, and single crystal X-ray crystallography of compound 3. Compounds 2 and 8 inhibited Mycobacterium tuberculosis H37Ra with an IC50 of 11.3 (IC90 of 20.0g/mL) and 12.5g/mL, respectively. Correspondingly, molecular docking studies with Extra Precision Glide revealed a correlation between score and biological activity for these compounds to describe the molecular basis for the most significant SAR results.
Keywords: alanine racemase; Anisochilus verticillatus; antimycobacterial activity; diterpenes; Lamiaceae

Two antibacterial spiro compounds from the roots of Artemisia pallens wall: evidence from molecular docking - Honmore, Varsha S.; Natu, Arun D.; Khedkar, Vijay M.; Arkile, Manisha A.; Sarkar, Dhiman; Rojatkar, Supada R. (Natural Product Research, 2022)
Bioassay-guided isolation from acetone extract of the roots of Artemisia pallens Wall yielded two spiro compounds (1 and 2). The structures of these compounds were determined on the basis of spectroscopic techniques such as IR, MS, 1 D and 2 D- NMR. The acetone extract, fractions and the isolated two compounds were investigated for their antibacterial activity against two gram negative (E. coli, P. aeruginosa) and two gram positive (S. aureus, B. subtilis) bacterial strains. Compound (2) showed the best spectra of activity with IC50 and MIC values between 2.48-3.08 and 12.78 - 21.77 mu M and Compound (1) with 2.57-3.69 and 38.17 - 80.57 mu M, respectively, for the four bacterial strains, whereas inactive against Mycobacterium tuberculosis. Molecular docking study could further help in understanding the various interactions between these compounds and DNA gyrase active site in detail and thereby could provide valuable insight into the mechanism of action.
Keywords: antibacterial activity; antimycobacterial activity; Artemisia pallens; Asteraceae; Molecular docking; spiro compound